Stellate Ganglion Block Combined with Dexmedetomidine Protects Obese Rats from Lipopolysaccharide-Induced Acute Lung Injury. (29th March 2022) - Zhang, Weiwei; Li, Pengfei; Gao, Xiang; Lv, Zhigan
Abstract : Objective . To investigate the effect and mechanism of combined stellate ganglion block (SGB) and dexmedetomidine (Dex) in obesity-related acute lung injury. Methods . Thirty-six 4-week-old male Wistar rats were randomly divided into 6 groups, each with 6 rats: blank group (Control), high-fat diet group (HFD), high-fat + lipopolysaccharide (LPS)-induced acute lung injury group (HFD + LPS), SGB group, Dex group, and SGB + Dex group. H&E staining detected the pathological structure of rat lung tissue. TUNEL staining was used to examine cell apoptosis in lung tissue. Oxidative factors were accessed by biochemical reagents. ELISA was employed to measure the levels of TNF- α, IL-1 β, and MCP1 in rat alveolar lavage fluid. Western blot detected the protein expression of glucose-regulated Protein 78 (GRP78), C/EBP homologous protein (CHOP), protein kinase R-like endoplasmic reticulum kinase (PERK), and p-PERK in lung tissue. Results . The body weight of rats in the HFD group was higher than that in the control group. The use of SGB or Dex alone could significantly reduce the rate of pulmonary edema and lung cell apoptosis in HFD-induced obese rats and reduce MPO, TNF- α, IL-1 β, and MCP1 levels, increasing the activity of SOD and GSH-Px. In addition, using SGB or Dex alone can also significantly reduce the protein expression levels of GRP78, CHOP, and p-PERK. The combined use of SGB and Dex can enhance the above effects. Conclusion . The combined use of SGB and Dex can protect against obesity-related acute lung injury and is more effective than using SGB or Dex alone.